(untitled) (Journal of the College of Basic Education, 2022)
Carrying strength is one of the important physical capabilities in the field of competitive sports, which affects the success of the sports training process and helps players to continue to perform skillfully, physically and tactically for as long as possible, and the capacity for endurance varies depending on the type of sports activities, it may sometimes be very short. And with a high level of intensity, such as gymnastics and wrestling movements, and it may be long, and with a medium level of intensity, as in basketball, football and other games.The research community represents a sample of Baghdad players for teams (football, basketball, handball, volleyball, wrestling, weightlifting) and for the sports season (2017-2018 AD) for ages under (16) years, and their number is (110) players, and their choice was deliberate because All players are from the city of Baghdad, and then data was generated for (110) players,